Material Rights of Children in Guardianship Maqashid al Sharia Perspective - Huzaimah, Arne; M. Tamudin (Nurani, 2024)
The material rights of children in the ruling of religious court judges are a very important issue to be studied in relation to the protection of children's rights in guardianship. This study, not only to explaining the protection of children's material rights but also analyzes the paradigm of determining children's material rights in guardianship in the Religious Court, and analyzes the urgency of children's material rights in the determination of guardianship from the perspective of maqashid al sharia. Employing a qualitative descriptive approach, the study gathered data by reading the judge's decision on guardianship and literature study. Data analysis was conducted by describing and interpreting the data inductively to reach a conclusion. The findings in this study reveals that the protection of children's rights in guardianship has been contained in positive law in Indonesia, but so far the ruling of the religious court judge on guardianship often do not explicitly accommodate the material rights of children clearly, so there is no protection of children's material rights in the judge's decision, while children's material rights are something that is very urgent to protect in the perspective of maqashid al Sharia at the level of maqashid al-daruriyyat in terms of safeguarding assets (hifz al-maal). The paradigm for determining the material rights of children in guardianship within religious courts is also included in the maqashid al hajiyyat group.